Modeling the Ecological Niche: A Case Study on Bioclimatic Factors Related to the Distribution of Phlebotomus tobbi Adler & Theodor (Diptera: Psychodidae) in Two Endemic Foci of Adana - Kavur, Hakan (Journal of medical entomology, 2019)
Cutaneous leishmaniasis (CL) is a zoonotic infectious disease caused mainly by Leishmania infantum Nicolle, 1908 (Kinetoplastida: Trypanosomatida) transmitted by dominant species Phlebotomus tobbi Adler & Theodor (Diptera: Psychodidae) in Adana, Turkey. CL has been reported to be detected commonly in low-socioeconomic status population scattered in rural areas. The environmental determinants are relatively poorly understood, especially in Adana despite the fact that Adana is endemic foci of CL. The subject of this study was the current and future probability model of P. tobbi in the study areas, and to determine the underlying factors affecting its distribution. Sticky papers and CDC light traps were used for capturing the sand fly specimens. The current and future presence of P. tobbi was modeled using maximum entropy (MaxEnt) techniques. The predictive model indicated the presence of P. tobbi in the southeast and south part of the selected study area with 0.816 area under the curve (AUC) value. The model also implied that its survival could tend to expand with suitable climatic conditions in future (2070) with 0.798 AUC value. In addition, aspect, digital elevation model, BIO3, BIO 10, BIO12, and BIO14 were determined as the most influential variables for current and projected future. ArcGIS and MaxEnt software were used for the ecological niche model analysis to explore the ecological conditions of the disease. I suggest that produced models contribute to better understanding of epidemiology and controlling of vector-borne diseases.